Lipoteichoic acid in Streptomyces hygroscopicus: structural model and immunomodulatory activities. - Marlène Cot (Public Library of Science (PLoS), 2011)
Gram positive bacteria produce cell envelope macroamphiphile glycopolymers, i.e. lipoteichoic acids or lipoglycans, whose functions and biosynthesis are not yet fully understood. We report for the first time a detailed structure of lipoteichoic acid isolated from a Streptomyces species, i.e. Streptomyces hygroscopicus subsp. hygroscopicus NRRL 2387T. Chemical, MS and NMR analyses revealed a polyglycerolphosphate backbone substituted with α-glucosaminyl and α-N-acetyl-glucosaminyl residues but devoid of any amino-acid substituent. This structure is very close, if not identical, to that of the wall teichoic acid of this organism. These data not only contribute to the growing recognition that lipoteichoic acid is a cell envelope component of gram positive Actinobacteria but also strongly support the recently proposed hypothesis of an overlap between the pathways of lipoteichoic acid and wall teichoic acid synthesis in these bacteria. S. hygroscopicus lipoteichoic acid induced signalling by human innate immune receptor TLR2, confirming its role as a microbe-associated molecular pattern. Its activity was partially dependant on TLR1, TLR6 and CD14. Moreover, it stimulated TNF-α and IL-6 production by a human macrophage cell line to an extent similar to that of Staphylococcus aureus lipoteichoic acid. These results provide new clues on lipoteichoic acid structure/function relationships, most particularly on the role of the polyglycerolphosphate backbone substituents.